Enhancing environmental health through the participation of stakeholders the case of the Mt. Makiling Forest Reserve, Philippines - Rebancos, Carmelita M. (2008)
The study described and assessed the different modes of participation of the three stakeholders in the protection and conservation of the Mt. Makiling Forest Reserve (MFR) to enhance environmental health. Key informant interview (KII) was used to gather data on the institution's vision and mission, its goals and objectives and its major projects and programs on Mt. Makiling. Secondary data on stakeholder participation and environmental health were analyzed to direct the researcher in the study. Results revealed that the types of the stakeholders' participation in the protection and conservation of MFR include implementing strategies and programs to create awareness on the importance of the MFR and providing funds for research projects and conduct of tree planting programs. Some of the activities cited in creating awareness consisted of information dissemination, photo exhibits, training and seminars. All stakeholders believed that their participation would enhance environmental health and hence, improve ecosystem services of the reserve.
Keywords: Mount Makiling Forest Reserve; Environmental health; Mount Makiling (Laguna) -- Conservation; Mount Makiling (Laguna) -- Protection; Forest reserves -- Los Baños (Laguna) -- Management